THE EFFECT OF MIND MAPPING LEARNING STRATEGY TO STUDENTS’ LEARNING RESULT ON EXCRETORY SYSTEM MATERIAL AT XI CLASS - Ummi Hiras Habisukan; Fajri Ismail; Yustina Hapida; Piski Ike Julianti (Al 'Ilmi : Jurnal Pendidikan MIPA, 2017)
This study aims to determine the effect of mind mapping learning strategy on student learning outcomes onexcretory system material in XI Science class. The research method used in this research is quasiexperimental method with design non - randomized Control Group Pretest-Postest Design . The population inthis study includes all XI science class in senior high school which amounts to 60 students. The samplingtechnique used sampling saturated with class XI Science 1 which amounted to 30 students as experimentalclass and class XI Science 2 which amounted to 30 students as control class. The instrument used in thisresearch is written test in the form of pretest and posttest to measure student learning result cognitively. Thefirst stage data analysis of the average value of pretest in experimental class is 47.50 while the control class is49.50. After applying the mind mapping strategy , the average grade of post experiment class increased withthe average value of 83.33 which is very good while the mean score of posttest of control class is 73,2 which isgood. The calculation results are known that there is influence a significant application of mindmapping learning strategy to student learning outcomes. Keywords: learning, mind mapping, result study, excretory system